Novel Discontinuous PWM Method for a Single-Phase Three-Level Neutral Point Clamped Inverter with Efficiency Improvement and Harmonic Reduction - Lee, June Seok; Kwak, Raeho; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2018)
This paper proposes a novel discontinuous pulse-width modulation (DPWM) method to reduce the current harmonics and improve the system efficiency for a single-phase three-level neutral-point clamped inverter. In single-phase inverters, the unipolar pulse-width modulation (UP-PWM) method is commonly used. However, this method has the disadvantage of power losses due to numerous switching operations. Conventional DPWM methods reduce the power losses and improve efficiency but increase the current total harmonic distortion (THD). To overcome these weaknesses, this paper proposes a hybrid DPWM switching method combining two PWM methods: the UP-PWM method and the conventional DPWM method called one-pole clamped PWM method. Since the proposed DPWM method offers all the advantages of both PWM methods, the optimal performance-with regard to the power losses and current THD-is obtained. The combination of two PWM methods is investigated by analyzing the power losses and current THD. Based on the analysis, the process determining the optimal operating condition is introduced. The effectiveness of the proposed DPWM method is demonstrated through simulations and experiments.
Keywords: Clamping method; Discontinuous pulse width modulations (DPWM); DPWM method; Three level NPC inverter; Three-level neutral point clamped; Total Harmonic Distortion (THD); Unipolar pulse width modulation; Unipolar PWM; Discontinuous pulse-width modulation (DPWM) method; switch-clamping method; three-level neutral-point clamped (NPC) inverter; unipolar PWM inverter